Autonomy support, light physical activity and psychological well-being in Rheumatoid Arthritis: A cross-sectional study. (March 2018) - Fenton, Sally A.M.; Veldhuijzen van Zanten, Jet J.C.S.; Metsios, George S.; Rouse, Peter C.; Yu, Chen-an; Kitas, George D.; Duda, Joan L.
Abstract: Background: Participation in physical activity may improve psychological well-being among people with Rheumatoid Arthritis (RA). This study examined the implications of autonomy support for physical activity, on objectively assessed light physical activity (LPA) engagement, and in turn, psychological well-being in RA. In addition, the role of lower-limb functional disability in these associations was investigated. Methods: RA patients (n = 50) completed questionnaires assessing 1) autonomy support for physical activity [from a patient-specified important other], 2) functional disability to 'rise' and 'walk' (functional disabilityRW), 3) depressive symptoms, and 4) subjective vitality. Levels of LPA [100–2019 counts/minute], were calculated from 7 days of accelerometry. Results: Path analysis supported a model ( χ 2 (2) = 2.44, p  = 0.30, CFI = 0.99, SRMR = 0.05, RMSEA = 0.07) in which important other autonomy support for physical activity significantly and positively predicted LPA engagement. In turn, LPA was significantly and positively associated with subjective vitality, and significantly and negatively linked to depressive symptoms. These associations were observed independently of adverse direct relationships between functional disabilityRW with depressive symptoms and subjective vitality. Conclusions: Important other autonomy support for physical activity may hold positive consequences for LPA engagement and related psychological well-being in RA, independent of the negative effects of lower-limb functional disability. Highlights: Light physical activity (LPA) may improve psychological well-being in Rheumatoid Arthritis (RA). Autonomy support (e.g. provision of choice and understanding) may encourage LPA participation to improve psychological health. This study examined associations between autonomy support, LPA and indices of psychological well-being in RA. Important other autonomy support for physical activity was positively associated with LPA engagement among people with RA. In turn, LPA predicted lower prevalence of depressive symptoms and higher subjective vitality in this patient group.